Staphylococcus microbes in the bovine skin microbiome attract blood-feeding stable flies - Nayani, Saif A.; Meraj, Sanam; Mohr, Emerson; Gries, Regine; Kovacs, Emma; Devireddy, Anand; Gries, Gerhard (Frontiers in Ecology and Evolution, 2023)
The human skin microbiome reportedly contributes to the attraction of mosquitoes to human hosts. We tested the hypothesis that bovine skin microbes affect the attraction of blood-feeding stable flies, Stomoxys calcitrans, to their bovine hosts. Microbes were collected from a calf and adult cow, and subsequently isolated and identified by mass spectrometry and genetic sequencing. Separate groups of (i) four Staphylococcus congeners (S. chromogenes, S. sciuri, S. simulans, S. succinus) and (ii) three bacterial heterogeners (Glutamicibacter protophormiae, Corynebacterium stationis, Wautersiella sp.) grown on agar, each attracted flies in still-air olfactometers, as did each Staphylococcus congener singly. The four Staphylococcus microbes also attracted flies in room bioassays. In greenhouse bioassays with paired black barrels as visual (surrogate host) stimuli, the treatment barrel baited with S. sciuri on agar induced significantly more fly alighting responses than the control barrel with sterile agar. This treatment effect could not be demonstrated on a cattle farm, possibly because of chemically and visually complex surroundings. Ammonia emitted by Staphylococcus microbes attracted flies, and a synthetic blend of microbe odorants enhanced the attractiveness of ammonia. Optimal attraction of stable flies to bovine microbes likely requires the integration of multimodal host cues.